2010
DOI: 10.1182/blood-2010-01-264333
|View full text |Cite
|
Sign up to set email alerts
|

Total Therapy 3 for multiple myeloma: prognostic implications of cumulative dosing and premature discontinuation of VTD maintenance components, bortezomib, thalidomide, and dexamethasone, relevant to all phases of therapy

Abstract: The impact of cumulative dosing and premature drug discontinuation (PMDD) of bortezomib (V), thalidomide (T), and dexamethasone (D) on overall survival (OS), event-free survival (EFS), time to next therapy, and post-relapse survival in Total Therapy 3 were examined, using time-dependent methodology, relevant to induction, peritransplantation, consolidation, and maintenance phases. Univariately, OS and EFS were longer in case higher doses were used of all agents during induction, consolidation (except T), and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 37 publications
(36 reference statements)
2
63
0
1
Order By: Relevance
“…The protocol details have been described previously, 20,21 as have imaging parameters for MBS, MRI and PET. 10,14 All radiographic studies were evaluated by radiologists who specialize in imaging of MM, each with more than a decade of experience in their respective field.…”
Section: Design and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocol details have been described previously, 20,21 as have imaging parameters for MBS, MRI and PET. 10,14 All radiographic studies were evaluated by radiologists who specialize in imaging of MM, each with more than a decade of experience in their respective field.…”
Section: Design and Methodsmentioning
confidence: 99%
“…Interestingly, four genes associated with high-risk disease (related to cell cycle and metabolism) were linked to counts of focal lesions detected by magnetic resonance imaging and positron emission tomography. The purpose of this study was to examine, among patients with newly diagnosed MM enrolled in the Total Therapy 3 (TT3) clinical trial, 20,21 the mutual correlation between MBS-OL counts and FL counts (defined by MRI and PET), and their associations with baseline prognostic variables.…”
Section: Introductionmentioning
confidence: 99%
“…Our position is that the philosophy for a cure should be based on the knowledge of those treatments that have demonstrated efficacy, and the investigation of optimal combinations, sequences, and of novel agents, instead of looking for soft replacements of equivalent efficacy that do not improve survival. Examples of this strategy are the results reported by Cavo et al, 23 and the total therapy programs developed by the Arkansas group 17,24 that integrate all treatment tolls through induction, consolidation and maintenance. This approach has resulted in a 4-year CR duration estimated at 89% in patients defined as low-risk by GEP, equivalent to Editorials and Perspectives haematologica | 2011; 96 (9)an estimated cure rate of 50%.…”
Section: -14mentioning
confidence: 99%
“…24 This group demonstrated that long-term disease control was feasible in myeloma and that cytogenetic abnormalities and baseline beta 2 microglobulin levels could predict long-term outcomes. 27,28 The recent experience with Total Therapy II and Total Therapy III has underscored the feasibility and efficacy of intensive induction followed by consolidation and maintenance as a strategy of obtaining high rates of CR and durable remissions in patients with standard-risk cytogenetic abnormalities. 27,28 Of particular interest has been defining risk groups according to gene-expression profiling that, if validated by others, will allow a more rational use of therapies in myeloma patients to achieve the overarching goal of maximum benefit with minimum burden of therapy.…”
Section: Role Of Autologous Sctmentioning
confidence: 99%
“…27,28 The recent experience with Total Therapy II and Total Therapy III has underscored the feasibility and efficacy of intensive induction followed by consolidation and maintenance as a strategy of obtaining high rates of CR and durable remissions in patients with standard-risk cytogenetic abnormalities. 27,28 Of particular interest has been defining risk groups according to gene-expression profiling that, if validated by others, will allow a more rational use of therapies in myeloma patients to achieve the overarching goal of maximum benefit with minimum burden of therapy. 29 However, what remains to be determined is whether such intensive induction therapy and posttransplantation consolidation is warranted for all patients with myeloma, or if it should be relegated to patients with specific risk categories.…”
Section: Role Of Autologous Sctmentioning
confidence: 99%